The macro-economic determinants of remittances: the case of Malawi - Muhoni, Eremia Great (Graduate School of Business (GSB), 2023)
In recent years, foreign remittances have increasingly played a crucial role in the balance of payments (BOP) of the majority of emerging nations. The remittances have surpassed various forms of capital inflows for several nations. At least in Malawi, however, very little has been done to comprehend this amazing expansion, despite the fact that the country is experiencing a considerable rise in remittances and a surge in interest in the potential of international transfers on a global scale. In order to better understand the macroeconomic factors that influence remittances to Malawi, the study looked at annual time series data from 1994 to 2020 for real gross domestic product, inflation rate, interest rate difference, and real effective exchange rate. The time series data was studied using Autoregressive Distributed Lag (ARDL) estimation techniques to explore the long run and short run effects The findings of the ARDL bounds show that the dependent and independent variables have a long-term relationship. According to the test results for short-run correlations between variables, there is no statistically significant correlation between remittances and the independent variables real gross domestic product, inflation rate, interest rate difference, and real effective exchange rate. In contrast to the inflation rate, which is strongly negatively correlated with remittances over the long term, real gross domestic product, interest rate difference, and real effective exchange rate are all significantly positively correlated with remittances. Finally, this study takes into account the relative significance of the long-term link found between remittances and the examined macro-economic variables, in addition to remittances as a reliable source of foreign exchange for development financing. The study recommends that the originating country's government, Malawi, needs to implement urgent and significant strategic macro-economic interventions and formulate appropriate policies to encourage its diaspora citizens to remit funds back home.